Life Expectancy after Bariatric Surgery in the Swedish Obese Subjects Study - Carlsson, Lena M.S; Sjöholm, Kajsa; Jacobson, Peter; Andersson-Assarsson, Johanna C; Svensson, Per-Arne; Taube, Magdalena; Carlsson, Björn; Peltonen, Markku (NEW ENGLAND JOURNAL OF MEDICINE, 2020)
This study compared long-term mortality and life expectancy among patients who underwent bariatric surgery or received usual obesity care in the Swedish Obese Subjects study and in persons in the SOS reference study. The adjusted median life expectancy with surgery was 3.0 years longer than in control patients but 5.5 years shorter than in the general population.